2009
DOI: 10.1186/1471-2458-9-405
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of pesticide storage before pesticide self-poisoning in rural Sri Lanka

Abstract: BackgroundDeliberate self-poisoning with agricultural pesticides is the commonest means of suicide in rural Asia. It is mostly impulsive and facilitated by easy access to pesticides. The aim of this large observational study was to investigate the immediate source of pesticides used for self-harm to help inform suicide prevention strategies such as reducing domestic access to pesticides.MethodsThe study was conducted in a district hospital serving an agricultural region of Sri Lanka. Patients who had self-pois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 20 publications
4
38
0
1
Order By: Relevance
“…Previous studies have shown that the incidence of pesticide poisoning varies quarterly in a year due to the season-specific agricultural activities, and the high incidence of pesticide poisoning correlates with pesticide availability during the farming season 7 8. Similarly, we found more pesticide poisoning and death cases in the farming season.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that the incidence of pesticide poisoning varies quarterly in a year due to the season-specific agricultural activities, and the high incidence of pesticide poisoning correlates with pesticide availability during the farming season 7 8. Similarly, we found more pesticide poisoning and death cases in the farming season.…”
Section: Discussionsupporting
confidence: 75%
“…In western countries, a large number of suicide deaths occur by hanging, while pesticide poisoning is a major cause of death in Asia and Latin America (Ajdacic-Gross et al, 2008;Konradsen et al, 2006;Konradsen et al, 2003;Mohamed et al, 2009;Roberts et al, 2003). There are also noticeable gender differences in the use of suicide methods in many countries, with females more likely to overdose on drugs or poisons, while men tend to use methods such as hanging and firearms (Hawton, Fagg, Simkin, Harriss, & Malmberg, 1998;Payne, Swami, & Stanistreet, 2008).…”
Section: Access To Suicide Methods (N = 21)mentioning
confidence: 99%
“…[5][6][7] However, no research has been performed to study this purchase of pesticides or to determine whether there might be ways to intervene to prevent poisoning events.…”
Section: Introductionmentioning
confidence: 99%